2013
DOI: 10.5901/jesr.2013.v3n9p127
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ICT in Teaching Science Education in Schools

Abstract: The place of ICT in teaching science education in schools cannot be over emphasized considering its promises in effective teaching and learning. This paper examine the role of ICT in teaching science education, its implication in both teaching and learning process and an attempt have been made to discuss the use of ICT in teaching and learning process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Pérez‐Sanagustín et al () suggested that ICT could improve students' science learning based on their review of the ICT literature. Relatedly, other researchers have reported that the science learning of students investigated in their studies was greatly enhanced by the use of ICT, which resulted in a better understanding of science overall (Abdullahi, ; Webb, , ). However, even though these studies were quite positive about the value of using ICT in science teaching and learning, it remains unclear whether specific ICT‐related aspects of students' learning are associated with their scientific literacy performance.…”
Section: Introductionmentioning
confidence: 86%
“…Pérez‐Sanagustín et al () suggested that ICT could improve students' science learning based on their review of the ICT literature. Relatedly, other researchers have reported that the science learning of students investigated in their studies was greatly enhanced by the use of ICT, which resulted in a better understanding of science overall (Abdullahi, ; Webb, , ). However, even though these studies were quite positive about the value of using ICT in science teaching and learning, it remains unclear whether specific ICT‐related aspects of students' learning are associated with their scientific literacy performance.…”
Section: Introductionmentioning
confidence: 86%
“…This generation witnessed the emergence of Google search engine, in 1998, and the foundation of Wikipedia, in 2001 (Koenigsberger, 2014). In addition, personal computers, office software, internet browsers, multimedia players, electronic encyclopedias and digital storage systems were massively implemented (Abdullahi, 2014).…”
Section: Rq3: At What Point and Through What Processes Did Informatio...mentioning
confidence: 99%
“…According to Chai et al [20], analyzing students' perceptions of learning with technology can contribute to enhancing educational programs. Abdullahi [21] posits that if educators receive sufficient training and are provided with more opportunities to engage with technology, their attitudes toward its incorporation in the classroom may evolve. Schuck and Kearney [22] discovered that students' attitudes toward Interactive White Boards (IWBs) tend to be more positive.…”
Section: Literature Reviewmentioning
confidence: 99%